2013
DOI: 10.1108/11766091311316176
|View full text |Cite
|
Sign up to set email alerts
|

Researching the lived experience of corporate governance

Abstract: PurposeThis literature review seeks to engage with the discussion of the limitations of studying corporate governance processes as a “black box” by developing a theoretical framework for qualitative corporate governance research that can support the design of future hermeneutic research into corporate governance practices.Design/methodology/approachThe approach is to develop a qualitative research framework based on the methodological discussions in the business and sociology literatures, and compare it with e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 65 publications
1
39
0
Order By: Relevance
“…We preferred this analysis to a formal bottom up/grounded theory coding process because we had, through our extensive prior discussions and readings, already a fairly developed idea of what we were looking for. Our data suggested that in the experience of the actors in Newcastle the budgeting developments were caught up in a larger narrative of fairness and politics (Ahrens and Khalifa, 2013), suggesting the significance of budgeting for the shaping of new accountability relationships.…”
Section: Methodsmentioning
confidence: 76%
“…We preferred this analysis to a formal bottom up/grounded theory coding process because we had, through our extensive prior discussions and readings, already a fairly developed idea of what we were looking for. Our data suggested that in the experience of the actors in Newcastle the budgeting developments were caught up in a larger narrative of fairness and politics (Ahrens and Khalifa, 2013), suggesting the significance of budgeting for the shaping of new accountability relationships.…”
Section: Methodsmentioning
confidence: 76%
“…But to properly research the lived experience of corporate governance, Ahrens and Khalifa (2013) advocate deep ethnographic descriptions.…”
Section: Future Research On Praxismentioning
confidence: 99%
“…Interview topics included the politics of planning, budgeting, reporting, and control practices. The purpose was to enable us to get a sense of the interviewees' lived experience of the local authority governance context (Ahrens and Khalifa, 2013). Moreover, contemporary and historical NCC governance, budgeting and performance management documentation was analysed.…”
Section: Research Approachmentioning
confidence: 99%